Geometric semantic GP with linear scaling - Nadizar, Giorgia (2024)
Nadizar, G., Sakallioglu, B., Garrow, F., Silva, S., & Vanneschi, L. (2024). Geometric semantic GP with linear scaling: Darwinian versus Lamarckian evolution. Genetic Programming And Evolvable Machines, 25(2), 1-24. Article 17. https://doi.org/10.1007/s10710-024-09488-0 --- Open access funding provided by Università degli Studi di Trieste within the CRUI-CARE Agreement. This work was partially supported by FCT, Portugal, through funding of research units MagIC/NOVA IMS (UIDB/04152/2020) and LASIGE (UIDB/00408/2020 and UIDP/00408/2020).